The rise of a mediated state in northern Kenya: the Wajir story and its implications for state-building - Menkhaus, Ken (Afrika Focus, 2008)
In an anarchic corner of northern Kenya in the mid-199os, a collection oflocal non-state actors led by a women’s market group created an umbrella movement that came to establish an impressive level of peace and security across an entire region. The Kenyan government forged a formal relationship with this group in Wajir, essentially sub-contracting out important functions oflocal government to local civic leaders, and using its partnership with the Wajir group as a template for similar state-sanctioned governance arrangements in other troubled border areas of the country. The Wajir story is examined in this article as an example of a "mediated state" approach to rebuilding rule oflaw through non-state actors in a conflict and post-conflict setting. Key words: mediated-state, state-building, civil society, peace-building,failed state, northern Kenya